Determination of anti-neutrophil cytoplasm antibodies (ANCA) specificity by immunofluorescence on chronic myelocytic leukemia cells - Chevailler, A; Noel, L H; Renier, G; Gardembas-Pain, M; Subra, J F; Nusbaum, P; Hurez, D; Lesavre, P (Journal of immunological methods, 1992)
ANCA positive sera, detected by the standard immunofluorescence method, derived from 37 patients with vasculitis were studied using formalin-acetone fixed chronic myelocytic leukemia cells (CML). All 37 sera were positive on CML cell smears. Furthermore formalin-actone fixation selectively impaired antinuclear antibody binding without reducing ANCA staining and thus facilitated differentiation of these autoantibodies which is often difficult with the standard immunofluorescence method. Two unequivocal and mutually exclusive ANCA binding patterns were identified using the CML smears: (1) type I with diffuse granular binding confined to the polymorphonuclear (PMN) cell lineage and preferentially staining immature cells; (2) type II with similar binding to the PMN cell lineage and, in addition, granular staining of the basophils. All type I antibodies were associated with a c-ANCA pattern suggesting that the major antigen recognized by these antibodies, recently identified as proteinase 3, is not detectable in basophils. The type II pattern was detected in both p-ANCA (84%) and c-ANCA (16%) positive sera. The type I sera remained positive on PMN cells from a myeloperoxidase (MPO) deficient subject and anti-MPO antibodies could not be detected in this group by ELISA. Conversely the type II pattern occurred in the presence of anti-MPO antibodies identified by immunofluorescence, ELISA and dot-blot with the exception of a single serum with antilactoferrin antibody. Type I binding only was observed in Wegener's granulomatosis (WG) but both patterns were found in microscopic polyarteritis (MPA) and rapidly progressive glomerulonephritis (RPGN).